The Effect of Giving Feedback on Improving The Basic Technical Ability of West Sumatra Junior Tennis Athletes - Suci Nanda Sari; Hendri Irawadi; Eko Purnomo (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
In Learning and Training, the element of feedback is very necessary and has a very good impact if done correctly. In this study, it aims to see the effect of providing direct and indirect feedback on the improvement of basic technical skills of West Sumatra junior tennis athletes. The sample in this study is 30 junior tennis athletes in the age category of 12-14 years. The results of the study show that 1) Providing direct feedback has a significant influence marked by the calculation of tcount 5.34> ttable 2.13. 2) Giving indirect feedback has a significant influence on the ability of basic techniques of court tennis marked by the calculation of tcount 4.65>t table 2.13. 3) Providing direct feedback is not more effective than providing indirect feedback on the basic technical ability of tennis by obtaining tcalculation 1.87 < ttable 2.13.